2006
DOI: 10.1016/j.devcel.2006.04.021
|View full text |Cite
|
Sign up to set email alerts
|

INCENP and Aurora B Promote Meiotic Sister Chromatid Cohesion through Localization of the Shugoshin MEI-S332 in Drosophila

Abstract: The chromosomal passenger complex protein INCENP is required in mitosis for chromosome condensation, spindle attachment and function, and cytokinesis. Here, we show that INCENP has an essential function in the specialized behavior of centromeres in meiosis. Mutations affecting Drosophila incenp profoundly affect chromosome segregation in both meiosis I and II, due, at least in part, to premature sister chromatid separation in meiosis I. INCENP binds to the cohesion protector protein MEI-S332, which is also an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
143
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 64 publications
18
143
2
2
Order By: Relevance
“…This model may explain why we observed an increased distance between sister kinetochores in CENP-50 -deficient cells after long nocodazole treatment (Minoshima et al, 2005). There are reports in which the pathway of cohesin removal, which requires PLK1, is proteolysis independent (Tang et al, 2004;Kitajima et al, 2005;Resnick et al, 2006). Our findings related to CENP-O class proteins are distinct from the proteolysis-independent pathway of cohesin removal.…”
Section: Discussioncontrasting
confidence: 37%
“…This model may explain why we observed an increased distance between sister kinetochores in CENP-50 -deficient cells after long nocodazole treatment (Minoshima et al, 2005). There are reports in which the pathway of cohesin removal, which requires PLK1, is proteolysis independent (Tang et al, 2004;Kitajima et al, 2005;Resnick et al, 2006). Our findings related to CENP-O class proteins are distinct from the proteolysis-independent pathway of cohesin removal.…”
Section: Discussioncontrasting
confidence: 37%
“…It has been previously shown that Aurora B is required for relocalization of Sgo from arms to centromeres (Resnick et al 2006;Boyarchuk et al 2007). Our results suggest that conversely, Sgo also contributes to the proper accumulation of the CPC at the inner centromere region.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora B is present in Xenopus extracts in the so-called chromosomal passenger complex (CPC), together with INCENP, survivin, and Dasra/ Borealin (Sampath et al 2004). The CPC is required for proper localization of Sgo and Bub1 in early mitosis (Vigneron et al 2004;Resnick et al 2006;Boyarchuk et al 2007). Importantly, we found that depletion of Sgo also alters the localization of CPC, but not the localization of Polo (Fig.…”
Section: Cohesin Distribution Is Affected By Sgo Depletionmentioning
confidence: 99%
“…A number of (candidate) substrates of Aurora B have been identified so far. 4,8,[12][13][14][15][16][17][18][19] Based on the previously reported phosphorylation sites for Aurora B kinase, the following consensus phosphorylation motif has been proposed: (R/K) 1-3 -X-(S/T) or (R/K)-(R/K)-X 0-2 -(S/T) where X denotes any amino acid. 15,20 However, few studies provide evidence for phosphorylation of the substrates by Aurora B in vivo, and even fewer studies report on the identification of the Aurora B-specific phosphorylation residues.…”
Section: Resultsmentioning
confidence: 99%